Compatibility Evaluation and Anatomical Observation of Melon Grafted Onto Eight Cucurbitaceae Species - Xiong, Mu; Liu, Changjin; Guo, Liping; Wang, Jin; Wu, Xiangshuai; Li, Ling; Bie, Zhilong; Huang, Yuan (Frontiers in Plant Science, 2021)
Melon (Cucumis melo) is one of the top 10 fruits in the world, and its production often suffers due to soil-borne diseases. Grafting is an effective way to solve this problem. However, graft incompatibility between scion and rootstock limits the application of melon grafting. In this study, the melon was grafted onto eight Cucurbitaceae species (cucumber, pumpkin, melon, luffa, wax gourd, bottle gourd, bitter gourd, and watermelon), and graft compatibility evaluation and anatomical observation were conducted. Taking melon homo-grafted plants as control, melon grafted onto cucumber and pumpkin rootstocks was compatible, while melon grafted onto luffa, wax gourd, bottle gourd, bitter gourd, and watermelon rootstocks was incompatible based on the scion dry weight on day 42 after grafting. Meanwhile, we found that starch–iodine staining of scion stem base is an index to predict graft compatibility earlier, on day 14 after grafting. Further, microsection observations showed that there was more cell proliferation at graft junction of melon hetero-grafted combinations; vascular reconnection occurred in all graft combinations. However, excess callose deposited at graft junction resulted in the blockage of photosynthate transport, thus, leading to starch accumulation in scion stem base, and finally graft incompatibility. In addition, undegraded necrotic layer fragments were observed at graft junctions of melon grafted onto incompatible bitter gourd and watermelon rootstocks. The above results provide clues for the selection and breeding of compatible Cucurbitaceae rootstocks of melon and demonstrate that starch accumulation in scion base and callose deposition at graft junction is associated with melon graft compatibility.